2019
DOI: 10.1177/1099800419889192
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of High-Sensitivity C-Reactive Protein and Homocysteine Levels With Disease Activity, Damage Accrual, and Cardiovascular Risk in Systemic Lupus Erythematosus

Abstract: Chronic inflammation coupled with cardiovascular disease (CVD) risk factors influences the progression of atherosclerosis in systemic lupus erythematosus (SLE). High-sensitivity C-reactive protein (hs-CRP) and homocysteine (Hcy) are associated with the risk of CVD in the general population, but their associations with CV risk and disease activity in SLE are unclear. In this cross-sectional study ( N = 139 SLE patients, mean age = 45.27 ± 13.18 years), we investigated associations between hs-CRP and Hcy levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Our results agree with previous studies conducted on SLE populations that reported a correlation between CRP levels and lipid profile alterations, diabetes, obesity, and BMI. They also found that triglyceride levels and the triglycerides/HDL-C ratio positively correlated with CRP levels [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results agree with previous studies conducted on SLE populations that reported a correlation between CRP levels and lipid profile alterations, diabetes, obesity, and BMI. They also found that triglyceride levels and the triglycerides/HDL-C ratio positively correlated with CRP levels [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mok et al reported that CRP levels were detectable in 77% of SLE patients, and CRP correlated with SLEDAI scores in SLE patients from USA [ 36 ]. Another study conducted on SLE patients from Spain also showed a significant correlation between CRP levels and the clinical disease activity assessed by the SLEDAI-2K score [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the patients with active SLE exhibited upregulation of TG and VLDL-C levels and downregulation of HDL-C levels, suggesting that dyslipidemia was aggravated in active SLE [22,24], demonstrating aggravated dyslipidemia in the patients with inactive SLE [25]. In accordance with these results, our study by univariate correlation analyses revealed negative correlations between SLEDAI and HDL-C, LDL-C, Apo A, and Apo B; positive correlations between SLEDAI and TG, and VLDL-C, also indicating that SLE disease activity is strongly associated with the changes of lipid profile.…”
Section: Discussionmentioning
confidence: 99%